PENGUATAN PROFIL PELAJARAN PANCASILA MELALUI SINERGI MULTIDISIPLIN BERBASIS TRANSPORMASI DIGITAL DALAM IMPLEMETASI KURIKULIM MERDEKA DI SMAN 2 BONE - Fadillah; Syarifuddin; Mimi Saswana; Dai Rahmat; Rezky Amelia Syahrami; Salsa Dwi Ridha Andini; Dwi Rahmadana; A. Nurul Aulia; Sulfiana; A. Aril Subastian; Sabda Ilahi; Subira Aulia Sukma; Nurfadhilah; Zakinah Mawadda; Arfah Yudah Pratama; Andi Muhammad Fatir; Edi Kurniawan; Adnan Annur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strengthening of the Pancasila Student Profile through multidisciplinary synergy based on digital transformation in the implementation of the Merdeka Curriculum at SMAN 2 Bone. The Pancasila Student Profile serves as an important foundation in shaping students who are characterized, creative, independent, critical thinkers, and capable of adapting to the development of digital technology. This study employed a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation involving teachers, students, and school stakeholders participating in the implementation of the Merdeka Curriculum. The results of the study indicate that multidisciplinary synergy through the integration of various subjects and the utilization of digital technology can enhance students’ engagement in the learning process. The implementation of digital transformation was carried out through the use of interactive learning media, digital platforms, and collaborative projects that support the strengthening of the values of the Pancasila Student Profile. In addition, the application of project-based learning in the Merdeka Curriculum encourages students to become more active, innovative, and capable of critical thinking in solving problems. Therefore, strengthening the Pancasila Student Profile through multidisciplinary synergy based on digital transformation can be an effective strategy to improve the quality of education and to shape students’ character in accordance with the demands of the digital era.